Impacto Emocional En El Distanciamiento Social de los estudiantes de la carrera de Psicopedagogía de la Universidad Nacional de Chimborazo - Parra Pérez, Andrea Carolina (2025)
The objective of this research work was to analyse the emotional impact on social distancing of students of the psychpedagogy career of the National University of Chimborazo. Social distancing is the way that society has considered implementing to protect against the spread of a disease by keeping the inhabitants in their homes they protect from possible contagion, the emotional impact is the alteration of our emotional state as a result of the experience of some type of situation that implies a los, intense, significant or prolonged damage or threat. It was considered necessary to carry out research that combines the methodology, that uses large samples and that provides a rigorous scientific vision of the psychological impact associated with the COVID-19 pandemic, the confinement in the educational population. Methodologically, it presented a quantitative approach with a non-experimental design; the level was correlational, due to its objectives it is basic; because of the place it is country. The population with which we worked were students of the National University of Chimborazo of the Psychpedagogy Career, with an intentional non-probabilistic sampling of 43 students in total of sixth and seventh semester. The instrument used for data collection was the DASS-21 Test to determine the emotional state of the students and an anonymous questionnaire was developed, in Spanish with questions on the Likert scale. It was disseminated to students of psychopedagogy by e-mail and its respective interpretation was elaborated. It was evident that the students were not significantly affected by their emotional state because of social distancing.